2009
DOI: 10.1249/mss.0b013e31818c6d93
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute and Chronic Exercise on Disulfide-Linked Growth Hormone Variants

Abstract: Acute resistance exercise leads to the appearance of disulfide-linked IRGH aggregates, and this response does not appear to be affected by 8 wk of chronic physical training. The physiological significance of increased proportions of disulfide-linked GH aggregates postexercise remains uncertain; however, structural alterations in GH moieties after acute exercise may represent important regulatory steps in mediating GH biological activity at selected target tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
(47 reference statements)
2
6
0
Order By: Relevance
“…The magnitude of increase ranged from 1.2-1.5× when compared to non-reduced samples, and this was primarily attributed to increased dimeric (30-60 kD) GH, as estimated by gel filtration chromatography [23]. In the current investigation, the magnitude of immunoreactive GH increase was 1.1-1.3×, a similar range to what has been reported elsewhere [22,24,26]. We believe these reports establish the validity of a simple chemical reduction procedure that can be used to estimate the effectiveness of an exercise regimen in releasing dimeric forms of GH into the circulation.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The magnitude of increase ranged from 1.2-1.5× when compared to non-reduced samples, and this was primarily attributed to increased dimeric (30-60 kD) GH, as estimated by gel filtration chromatography [23]. In the current investigation, the magnitude of immunoreactive GH increase was 1.1-1.3×, a similar range to what has been reported elsewhere [22,24,26]. We believe these reports establish the validity of a simple chemical reduction procedure that can be used to estimate the effectiveness of an exercise regimen in releasing dimeric forms of GH into the circulation.…”
Section: Discussionsupporting
confidence: 87%
“…Serum GH was reduced in accordance with previously described methods [24]. In summary, serum aliquots were thawed and split into two 135 μL portions.…”
Section: Gsh Gh Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The programs were similar in daily duration and approximate intensity, allowing us to attribute any training group diVerences to program type rather than duration or intensity of exercise training. A typical week of training for the CT and RT groups are depicted in Table 1 (Pierce et al 2009). …”
Section: Exercise Trainingmentioning
confidence: 99%
“…The effects of exercise, both resistance and aerobic, have been shown to increase the proportion of non-22 kDa GH isoforms and thereby potentially enhance a diabetogenic effect and prevent postexercise hypoglycemia [21]. More recently, it has been shown that acute resistance may lead to the appearance of disulfide-linked GH aggregates for which the physiological significance remains uncertain [28]. …”
Section: Introductionmentioning
confidence: 99%